COMMUNICATION POTENTIAL OF THE INDIVIDUAL AS AN OBJECT FOR SPECIAL EDUCATIONAL INTERVENTION WITHIN THE SYSTEM PROMOTING COMMUNICATION ACTIVITY DEVELOPMENT FOR CHILDREN WITH SYSTEM SPEECH DISORDERS - Martynenko, I. (Педагогічна освіта: Теорія і практика. Психологія. Педагогіка., 2017)
The article presents the findings of the empirical study on the developmental level of communication toolkit of senior preschool children with system speech disorders of primary origin. Communication toolkit is an individual peculiar complex of an individual’s communication traits (interpersonal, social and psychological), which describe his or her current abilities in exercising communication components of different activities. The given structure has a significant impact on communication outcomes and further socialization of children with system speech disorders. It has been discovered that specific development of preschooler’s personal communication traits causes difficulties in communication on a basic and operational levels, evoke lack of iniative during communication and structural deficiency of communication activity. Based on research outcomes, the author has elaborated personal profile of a child with system speech disorders. In order to harmonise communication activity structure of children with system speech disorders, the author introduces psychological system promoting its development, a significant part of which is devoted to development of communication potential of the given category of children. Communication potential is treated as individually specific system of a child’s communication inclinations, which can be actualised through activity of communication subject. Corrective and educational intervention aiming at developing communication potential requires active involvement of an adult who facilitates the process and provides comfortable psychological environment for the child’s communication traits to be manifested.